Multilocus sequence typing, biochemical and antibiotic resistance characterizations reveal diversity of North American strains of the honey bee pathogen Paenibacillus larvae - Krongdang S. (2017)
Paenibacillus larvae is a Gram positive bacterium and the causative agent of the most widespread fatal brood disease of honey bees, American foulbrood (AFB). A total of thirty-three independent Paenibacillus larvae isolates from various geographical origins in North America and five reference strains were investigated for genetic diversity using multilocus sequence typing (MLST). This technique is regarded to be a powerful tool for epidemiological studies of pathogenic bacteria and is widely used in genotyping assays. For MLST, seven housekeeping gene loci, ilvD (dihydroxy-acid dyhydrogenase), tri (triosephosphate isomerase), purH (phospharibosyl-aminoimidazolecarboxamide), recF (DNA replication and repair protein), pyrE (orotate phosphoribosyltransferase), sucC (succinyl coenzyme A synthetase β subunit) and glpF (glycerol uptake facilitator protein) were studied and applied for primer designs. Previously, ERIC type DNA fingerprinting was applied to these same isolates and the data showed that almost all represented the ERIC I type, whereas using BOXPCR gave an indication of more diversity. All isolates were screened for resistance to four antibiotics used by U.S. beekeepers, showing extensive resistance to tetracycline and the first records of resistance to tylosin and lincomycin. Our data highlight the intraspecies relationships of P. larvae and the potential application of MLST methods in enhancing our understanding of epidemiological relationships among bacterial isolates of different origins.